2015
DOI: 10.1149/2.0031507jss
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Bonding with Polydimethylglutarimide Based Lift Off Resist as a Layer Transfer Platform

Abstract: Bonding of lift off resist (LOR) was performed to realize temporary wafer bonding without residue. Bonding process conditions such as spin speed, pre-bake temperature, and bonding temperature were optimized to obtain a large bonded area with high bond strength. Under optimized process conditions, a bonded area covering over 98% of the wafer surface, with a room temperature bond strength of nearly 5 J/m 2 is achieved. During razor blade testing, fracture often occurs at the Si wafer. Moreover, debonding using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Micro Chem developed a lift-off resist (LOR) material (polydimethyl glutarimide) for wafer-to-wafer bonding and demonstrated that the LOR material could be resolved in NMP-based solvents [46]. Thermoset polymers have greater thermal and chemical stability compared to thermoplastic materials.…”
Section: Chemical Dissolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro Chem developed a lift-off resist (LOR) material (polydimethyl glutarimide) for wafer-to-wafer bonding and demonstrated that the LOR material could be resolved in NMP-based solvents [46]. Thermoset polymers have greater thermal and chemical stability compared to thermoplastic materials.…”
Section: Chemical Dissolutionmentioning
confidence: 99%
“…Special technologies such as ZoneBOND ® [40] and air-jetting were developed [41,42]. In addition, hydrogenated amorphous silicon (a:Si-H) [22,43] and various polymers, such as polyelec-trolyte [44], iCVD polyglycidylmethacrylate (PGMA) [45] and polydimethylglutarimide (PMGI) [46], have also been used as temporary bonding materials. Here, we review the corresponding temporary bonding materials, principles, applications and future trends according to different debonding methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a wafer bonding method for polymethylglutarimide (PMGI) was proposed for layer transfer. 4 PMGI is a lift-off resist (LOR) material and is traditionally used as a sacrificial layer for the undercutting process during lift-off processing. [5][6][7] Moreover, our research group has demonstrated that the PMGI layer can be effectively bonded using thermal compression bonding.…”
mentioning
confidence: 99%
“…Debonding using N-methyl-2-pyrrolidone (NMP) results in negligible amounts of the PMGI sacrificial layer residue on the debonded wafer surface and is therefore suitable for a transfer process. 4,9 However, thermal compression bonding materials require higher temperatures than the glass transition temperature (T g ) of the polymer material. In our previous bonding study, a bonding temperature of 250 • C was required for bonding most of the loaded area.…”
mentioning
confidence: 99%
See 1 more Smart Citation